Plasmonic properties and sensor application of the Ag nanocaps. (February 2022) - Wang, Ziyun; Zheng, Xuanli; Gao, Mengyao; Zhao, Jintian; Lan, Jinshen; Ye, Xiaofang; Wan, Jing; Fei, Yuchen; Guo, Shengshi; Wu, Yuanfei; Huang, Shengli; Li, Shuping; et al.
Abstract: Plasmonic properties of the Ag nanocaps were analyzed by the finite-difference time-domain method, in addition to the fabrication and sensor application of the two-dimensional Ag nanocap arrays. The thickness limitation for the light penetration of the nanocaps was revealed. The evolution of the plasma modes with the shell thickness and structure of the nanocaps was illustrated. The hemisphere nanocap was found to own the strongest absorption intensity and field enhancement. The sensing ability of the fabricated Ag hemisphere nanocap arrays was evaluated by the Raman spectrum of the rhodamine 6G and methylene blue molecules. The ordered arrays displayed improved light absorption with intense plasmon coupling, resulting in the strong surface-enhanced Raman scattering with an enhanced factor 15 folds of the nanosphere arrays, which suggested that the metal nanocaps might be promising for biochemical sensor application. Graphical abstract: The ordered nanocaps owned strong light absorption and confined electric field around with enormous plasmon coupling, resulting in the improved surface-enhanced Raman scattering with an enhanced factor 15 folds of the ordered nanospheres. Image 1 Highlights: A certain thickness limitation for the light penetration of the Ag nanocaps was revealed. The evolution of the plasma modes with the shell thickness of the caps was illustrated. The development of the plasma modes with the cap structure was illustrated. The Ag nanocap arrays confined electric field around the nanocaps with strong plasmon coupling. The Ag nanocap arrays achieved an enhanced factor as large as 15 folds of the Ag/PS nanosphere arrays.